Changes in blood variables in elite cross-country skiers during season - Damsgaard, R. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
The use of various drugs that stimulates erythropoiesis has been found in athletes competing in endurance events. To aid in limiting the occurrence of this form of doping, blood screening methods has been suggested (Parisotto et al., 2000) to target for proper timing of test for exogenous erythropoietin (rHU-EPO) in urine. Which blood variables to use has been debated, and to gain some more insight FIS established an individual blood profile programme in November 2000 in which hemoglobin ([Hb]) and reticulocytes were measured. The specific aims were two fold. First, to illustrate the individual "in season" fluctuations of [Hb] and reticulocytes in elite cross-country skiers. Secondly, to investigate whether the introduction of reticulocytes could be utilized as sensitive biomarker of possible rHU-EPO use. In total 346 individuals, 226 males and 120 females, were tested on various occasions from the season 2000-01 until 2004-05. The blood samples were analysed on site for [Hb] and reticulocytes. The introduction of an extensive blood sampling procedure by FIS had a dramatic effect on mean [Hb]; The Hb values today are in the normal range. The "in season" fluctuations in [Hb] and reticulocytes are on average 1 g/dL (range 0.1-4.0) and 0.3% (range 0.1-1.6), respectively. The determination of reticulocyte count facilitates the interpretation of the variations in individual [Hb] values. Our data suggests that if a simultaneous increase in [Hb] and reticulocyte values is present or a sudden drop in reticulocyte count in combination with an ongoing increase in Hb is found, target tests for blood stimulating substances should be performed. In conclusion, reticulocytes appears to be a sensitive reflection of elevated, stable or reduced erythropoiesis and is then a good a good blood variable in screening for blood stimulating substances.